Easy Direct Functionalization of 2D MoS2 Applied in Covalent Hybrids with PANI as Dual Blend Supercapacitive Materials - Matteo Crisci; Felix Boll; Sara Domenici; Jaime Gallego; Bernd Smarsly; Mengjiao Wang; Francesco Lamberti; Andrea Rubino; Teresa Gatti (Advanced Materials Interfaces)
Abstract The pressing demand for more sustainable energy provision and the ongoing transition toward renewable resources underline the critical need for effective energy storage solutions. To address this challenge, scientists persistently explore new compounds and hybrids and, in such a dynamic research field, 2D materials, particularly transition metal di‐chalcogenides (TMDCs), show great potential for electrochemical energy storage uses. Simultaneously, also conductive polymers (CPs) are interesting and versatile supercapacitor materials, especially polyaniline (PANI), which is extensively studied for this purpose. In this work, a powerful method to combine TMDCs and PANI into covalently grafted hybrids starting from aniline functionalized few‐layers 1T‐MoS2, attained by a facile direct arylation with iodoaniline, is presented. The hybrids provide circa 70 F g−1 specific capacitance in a pseudo device setup, coupled with a robust capacitance retention of well over 80% for up to 5000 cycles. These findings demonstrate the potential of similar covalent composites to work as active components for novel, innovative energy storage technologies. At the same time, the successful synthesis marks the efficacy of direct covalent grafting of conductive polymer on the surface of 2D TMDCs for stable functional materials.